A mixed-methods study of online learning in the EFL classroom - Carolina Girón-García; Sorina Boghiu-Balaur (Revista de Lingüística y Lenguas Aplicadas)
The need to adapt classroom materials to maintain students’ interest to learn the subject matter in an engaging environment, by means of Information and Communication Technologies, becomes a first concern. The purpose of this mixed-methods study, which involves a combination of both qualitative and quantitative data analyses, is to survey the perceptions and engagement of higher education students as regards learning theoretical content and vocabulary through the implementation of two online called ‘Cybertasks’. The participants were administered two perception questionnaires in order to gather information concerning their previous knowledge and their acquired knowledge. Additionally, a final written exam was delivered to determine whether there is a correlation between students’ satisfaction with Cybertask completion and their academic achievement. The results indicate that students with higher levels of engagement towards the use of the Cybertask to improve their acquisition of theoretical content and vocabulary showed higher academic achievement in their final exam.